Culture Talk and the Politics of the New Right: Navigating Gendered Racism in Attempts to Address Violence against Women in Immigrant Communities. - Abji, Salina; Korteweg, Anna C.; Williams, Lawrence H. (Signs: Journal of Women in Culture & Society)
Right-wing policy approaches addressing violence against women often draw from xenophobic conceptions of racialized groups as culturally backward. While antiracist, anticolonial feminist scholarship has convincingly critiqued this, how to talk about culture in a context of gendered racism remains pressingly unresolved. In our work, we examine how the politics of culture shape policies and practices designed to combat violence against women in the Canadian immigration context. Using interviews with fifteen service providers conducted in 2011–12 during a time of heightened attention to violence against women among South Asian immigrants, we show how advocates challenged stigmatizing conceptions of violence as cultural, rejecting what we call "culture talk" in favor of more structural explanations. However, advocates also struggled to account for what we would call the "cultural specificities" of the violence they witnessed, often substituting the term "community" for "culture" to avoid racialization. We then analyze parliamentary debates surrounding the 2015 right-wing Conservative government passage of the Zero Tolerance for Barbaric Cultural Practices Act, which targeted forced marriage, polygamy, and honor-based violence. Right-wing politicians incorporated both "culture" and "community" to deflect accusations of racism while nevertheless engaging in racializing discourse, illustrating the limits of the turn to "community." Acknowledging the dangers of culture talk, our analysis builds on feminist scholarship to call for renewed approaches to talking about culture—not as a totalizing force but as situated practices of meaning making that inform all acts of violence and responses to violence.